Marcatge posicional i prominència en el vocalisme àton - Lloret, Maria Rosa; Jiménez, Jesús (Caplletra. Revista Internacional de Filologia, 2008)
It has long been noticed that more perceptible elements tend to associate to positions that are structurally stronger to the end that several prominent features converge in the same site; and vice versa: elements of low perceptibility prototypically associate to less prominent positions ("positional markedness"). The main aim of this paper is to present the effects of positional markedness in the a-tonic vowel system of Catalan through the analysis of two cases that have not been studied in depth, i.e. the occurrence of different epenthetic vowels according to the position in which they appear in Alghero and western Catalan, and the presence of different patterns of vowel reduction in western Catalan. We further extend the analysis to cases of deletion in eastern Catalan as well as to cases of contextual epenthesis and vowel reduction in other languages.